The effect of month and breed on plasma adrenocorticotropic hormone concentrations in equids. (August 2022) - Durham, A.E.; Potier, J.F.; Huber, L.
Abstract: Use of plasma adrenocorticotropic hormone (ACTH) concentrations for the diagnosis of PPID in equids requires awareness of other factors that might influence ACTH concentrations, including breed and time of year. This study was designed to investigate effects of breed on plasma ACTH concentrations and potential interactions between breed and time of year. Ten breeds were selected from a laboratory database containing data on plasma ACTH concentrations. Breeds represented were Arabians, Cobs, Connemara ponies, donkeys, Irish Sports horses, New Forest ponies, Shetland ponies, Thoroughbreds, Warmbloods and Welsh breeds. Multivariable analysis was used to determine the effects of month and breed on plasma ACTH concentrations. A circannual pattern of ACTH concentration was documented, with a nadir in April and a peak in September. Arabian horses and donkeys had significantly higher ACTH concentrations than some other breeds, primarily from May to November, whereas in Shetland ponies and Welsh breeds, relatively higher ACTH concentrations only occurred from July to November. The annual increase in plasma ACTH appeared to commence in late April/early May in response to increasing daylight and decreased again promptly after the late September equinox as daylength fell below 12 h per day. Inter-breed differences in plasma ACTH were substantial and indicated that breed and time of year should be considered when interpreting plasma ACTH concentrations in equids suspected for PPID. Highlights: Nadir in adrenocorticotrophic hormone (ACTH) concentration occurred in April. Peak ACTH concentrations occurred in September. Day length appears to control the circannual rhythm in plasma ACTH. Arabians and donkeys had higher ACTH concentrations primarily from May to November. Shetland and Welsh ponies had higher ACTH concentrations from July to November.